PELAYANAN TRANSPORTASI UMUM (TRANS METRO PEKANBARU) TERHADAP MASYARAKAT PENYANDANG DISABILITAS DI KOTA PEKANBARU - Rahmani, Anggun Tripanti Rahmani; Harirah, Zulfa (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2024)
This research departs from several phenomena that are a problem, namely that Pekanbaru Transmetro stops still do not meet standards and are not equipped with facilities for people with disabilities. Then the condition of the buses still does not provide opportunities for passengers with disabilities. The research was conducted using a qualitative descriptive method which aims to describe the phenomena that occur. The data collection techniques used in this research were interviews, observation, documentation as well as note taking and recording. Indicators of inclusive public services according to Agus Dwiyanto (2015) include: quality of policies, service procedures, discretionary space and gender prioritization. The results of this research show that overall, the inclusive services carried out by the Trans Pekanbaru Management UPT in implementing public services for people with disabilities are not optimal. This can be seen from the fact that there are still many deficiencies in the provision of facilities in the form of bus stops, sidewalks and so on. The quality of policy still has many problems that need to be resolved. So there is a need for clear and written regulations regarding TMP bus services for people with disabilities. Service procedures are quite good, this is proven by the existence of SOPs regarding corridor operation procedures and SOPs regarding TMP bus services which have been implemented seriously, then there is dissemination of information to the public regarding TMP bus schedules and routes as well as all the information needed by the public. Discretionary space was chosen by providing participatory services. In its implementation there were several problems regarding the condition of the TMP bus stops, which were not all in accordance with the needs of people with disabilities. Gender mainstreaming is carried out by upholding the value of justice, this is realized through the provision of disabled-friendly facilities, so that disabled people feel they are getting justice when they access TMP bus services. Keywords: Inclusive Services, Persons with Disabilities, Trans Metro Pekanbaru, Pekanbaru City